Solution equilibria of cytosine- and guanine-rich sequences near the promoter region of the n-myc gene that contain stable hairpins within lateral loops - Benabou, Sanae; Ferreira, Rubén; Aviñó, Anna; González, Carlos; Lyonnais, Sébastien; Solà, Maria; Eritja, Ramon; Jaumot, Joaquim; Gargallo, Raimundo (Biochimica et biophysica acta, 2014)
Cytosine- and guanine-rich regions of DNA are capable of forming complex structures named i-motifs and G-quadruplexes, respectively. In the present study the solution equilibria at nearly physiological conditions of a 34-base long cytosine-rich sequence and its complementary guanine-rich strand corresponding to the first intron of the n-myc gene were studied. Both sequences, not yet studied, contain a 12-base tract capable of forming stable hairpins inside the i-motif and G-quadruplex structures, respectively. Spectroscopic, mass spectrometry and separation techniques, as well as multivariate data analysis methods, were used to unravel the species and conformations present. The cytosine-rich sequence forms two i-motifs that differ in the protonation of bases located in the loops. A stable Watson–Crick hairpin is formed by the bases in the first loop, stabilizing the i-motif structure. The guanine-rich sequence adopts a parallel G-quadruplex structure that is stable throughout the pH range 3–7, despite the protonation of cytosine and adenine bases at lower pH values. The presence of G-quadruplex aggregates was confirmed using separation techniques. When mixed, G-quadruplex and i-motif coexist with the Watson–Crick duplex across a pH range from approximately 3.0 to 6.5. Two cytosine- and guanine-rich sequences in n-myc gene may form stable i-motif and G-quadruplex structures even in the presence of long loops. pH modulates the equilibria involving the intramolecular structures and the intermolecular Watson–Crick duplex. Watson–Crick hairpins located in the intramolecular G-quadruplexes and i-motifs in the promoter regions of oncogenes could play a role in stabilizing these structures. •Two novel cytosine- and guanine-rich regions at the promoter of the n-myc gene are studied.•Both sequences show unusual long loop which likely forms a stable hairpin structure.•Spectroscopy, chromatography, and multivariate analyses are used.•The formation of i-motif and G-quadruplex is demonstrated.